Analisis Brand Switching Penggunaan Aplikasi Food Delivery Order Online dengan Menggunakan Metode Rantai Markov oleh Mahasiswa Universitas Udayana Di Jimbaran Bali - Siahaan, Frida M; Wiranatha, Anak Agung Putu Agung Suryawan; Wijaya, I Made Mahaputra (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2023)
Online food delivery orders are a means of connecting consumers with online culinary businesses. This study aims to determine the characteristics of consumers , especially Unud students who live in the Udayana University Jimbaran Bali campus environment who use online food delivery orders, and analyzing the possibility of brand switching from several online food delivery order platforms used in the next five years, as well as predicting a market share balance that will occur in the long term. The data used in this study is primary data collected by distributing questionnaires to 100 students as respondents. Analysis of brand switching and market share balance using the Markov Chain method with the help of QM 5.3 for Windows software. The results showed that characteristics of student respondents who became online food delivery order customers were dominated by women aged around 21-23 years, and amount of expenditure to buy food and drinks online was around IDR 500,000-IDR 1,000,000/month. with an average of 2- 3 orders/week. The reason for respondents using food delivery services is practicality ordering food, and taking advantage of existing promotions. Respondents found information about the platform from social media advertisements. The market share of the online food delivery order platform in first period is known to be Gofood leading with a market share of 43%, Grabfood (17%) Shopeefood (38%) and other platforms (2%). second period there will be a decrease from Gofood to 40.88%, Grabfood (15.76%) and an increase on the Shopeefood platform to 40.36% and other brands (3%). In third period and onwards there will be changes the market share of each platform, and in fifth period Gofood's market share will drop to 40.26%, Grabfood (15.01%), but Shopeefood will increase to 41.70% and other brands ( 3.03%). The equilibrium point is predicted to be reached in the 71st period, with Gofood's market share of 41.0%, Grabfood (15.4%), Shopeefood (42.5%) and other platforms (3.1%).   Keywords: Brand Switching, Markov Chain, Gofood, Grabfood, Shope foo d   Food delivery order online merupakan sarana penghubung konsumen dengan usaha kuliner secara online . Penelitian ini bertujuan untuk mengetahui karakteristik konsumen khususnya mahasiswa Universitas Udayana yang tinggal di lingkungan kampus Universitas Udayana Jimbaran Bali pengguna food delivery order online , dan menganalisis kemungkinan terjadinya brand switching dari beberapa platform food delivery order online yang digunakan dalam lima tahun kedepan, serta memprediksi terjadinya keseimbangan pangsa pasar yang terjadi dalam jangka panjang. Data yang digunakan dalam penelitian ini adalah data primer yang dikumpulkan melalui penyebaran kuesioner kepada 100 mahasiswa sebagai responden. Analisis brand switching dan keseimbangan pangsa pasar menggunakan metode Rantai Markov ( m arkov c hain ) dengan bantuan software QM 5.3 for Windows . Hasil penelitian menunjukkan karakteristik responden mahasiswa menjadi pelanggan food delivery order online didominasi perempuan, usia sekitar 21-23 tahun, besarnya pengeluaran pembelian makanan/minuman secara online sekitar Rp.500.000-Rp.1.000.000 per bulan, dengan rata-rata melakukan 2-3 kali pemesanan per minggu. Alasan responden menggunakan jasa pesan-antar makanan adalah kepraktisan melakukan pemesanan makanan, dan memanfaatkan promosi. Responden mengetahui informasi platform food delivery order online dari iklan media sosial. Pangsa pasar dari platform food delivery order online   periode 1 diketahui Gofood memimpin dengan pangsa pasar sebesar 43%, Grabfood (17%) Shopeefood (38%) dan platform lainnya (2%). Periode 2 terjadi penurunan Gofood menjadi 40,88%, Grabfood (15,76%) dan peningkatan Shopeefood 40,36% dan merek lainnya (3%). Periode 3 dan seterusnya terjadi perubahan pangsa pasar masing-masing platform, dan pada periode 5 pangsa pasar Gofood turun menuju 40,26%, Grabfood (15,01%), namun Shopeefood mengalami peningkatan menjadi 41,70% dan merek lainnya (3,03%). Titik ekuilibrium diprediksi tercapai pada periode ke 71, dengan pangsa pasar Gofood sebesar 41,0%, Grabfood (15,4%), Shopeefood (42,5%) dan platform lainnya (3,1%).   Kata kunci: Brand Switching, Rantai Markov , Gofood, Grabfood, Shopeefood